Evaluation of Macular Pigment Optical Density in Healthy Eyes Based on Dual-Wavelength Autofluorescence Imaging in South Indian Population - Srinivasan, Ramyaa (Transl Vis Sci Technol, 2020)
PURPOSE: To estimate macular pigment optical density (MPOD) values across different age groups in the South Indian population across various spatial profiles using dual-wavelength autofluorescence. METHODS: Sixty eyes of 31 healthy subjects underwent MPOD measurement with Spectralis HRA+OCT. The average MPOD and macular pigment optical volume (MPOV) at 1°, 2°, and 6° radii, the mean MPOD in the classical Early Treatment Diabetic Retinopathy Study (ETDRS) grid, and the spatial profiles of two different age groups across 12 plots covering the radial sectors were recorded. RESULTS: The mean age was 39.1 ± 12.7 years. The mean MPOD and MPOV values were 0.38 ± 0.11 and 787.95 ± 225.13 at 1° eccentricity, 0.23 ± 0.08 and 2000 ± 708.24 at 2° eccentricity, and 0.05 ± 0.02 and 4335 ± 2007.71 at 6° eccentricity, respectively. In the ETDRS grid, the mean MPOD was found to be highest in the central sector and lowest in the inferior peripheral ring. We also found that along the radial sectors the lower quadrants tended to have low MPOD as compared to the upper quadrants. Subjects 40 years of age or older had significantly higher averaged MPOD in certain areas (–15° to 15° and 75° to 105°) along the radial sectors than subjects less than 40 years of age. CONCLUSIONS: This study establishes a reference value for future studies of diseased eyes in the South Indian population. TRANSLATIONAL RELEVANCE: Our study is unique in that it reports MPOD among the South Indian population across different age groups, as well as the distribution of MPOD in all nine zones of the classical ETDRS grid and various spatial profiles covering the 30° radial sectors centered on the fovea.